AN INTRODUCTOY REFLEXION ON POLEMOS IN HERACLITUS' DK 53 - Luiz, Felipe [UNESP] (Paulus Editora, 2020)
The thought of Heraclitus from Ephesus continues to interest us in spite of the millennia that apart us from it. The aim of this paper is to articulate some interpretative questions on terms of the fragment 53 DK, in which Heraclitus use the concept polemos, that is, war.
Keywords: Heraclitus of Ephesus; polemos; ontology; Ancient Philosophy